2022
DOI: 10.5377/nexo.v35i03.15007
|View full text |Cite
|
Sign up to set email alerts
|

Features of the use of information modeling technology in the activities of the construction complex enterprises in risk conditions

Abstract: The article is devoted to new scientific approaches and practical recommendations for the use of information modeling technology in the activities of the construction complex enterprises at the life cycle stages of the construction of real estate objects in risk conditions. Research methods are theoretical analysis and empirical research. The object of the study is the construction complex enterprises in the conditions of the factor space formation at all stages of the life cycle. Quantification of factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Based on the above, the activity of the investor (developer, customer) and other participants at all stages of the investment cycle is a rather lengthy and complex process and therefore must be carried out taking into account a certain perspective. The formation of the directions of this activity, taking into account the perspective, is the process of developing an investment strategy [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above, the activity of the investor (developer, customer) and other participants at all stages of the investment cycle is a rather lengthy and complex process and therefore must be carried out taking into account a certain perspective. The formation of the directions of this activity, taking into account the perspective, is the process of developing an investment strategy [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…It is required to improve the methodology of analysis and its practical approbation in the construction industry. The results of studying the activities of construction enterprises showed that the practice of management analysis lags far behind the theory [2].…”
Section: Resultsmentioning
confidence: 99%
“…The concept of the object information model includes a set of interconnected data, documents, materials about the construction object stored in software form, and they can be either similar or different at each stage of the life cycle of the object, including at the stages of engineering surveys, architectural and construction design, construction, reconstruction, capital repairs, operation and (or) demolition of the capital construction object. The use of such method of recording information in electronic digital format for all participants in the construction process, which is one of the main organizational and economic mechanisms for the functioning of the enterprises of the construction complex, increases their competitiveness in the real estate market, as well as the quality of the products produced directly, which ultimately leads to a decrease in its cost (Khrustalev, 2014, P.G. Grabov, 2019, N.A.…”
Section: Methodsmentioning
confidence: 99%
“…Previously performed works by Khrustalev (2007Khrustalev ( , 2014, P. Grabov (2017,2019,2021), K. Grabov (2022), Grebenshchikov, 2017, Vyatskova (2015, 2016, Belyakov (2017), Garcia (2023), Bizarria, (2021) show the relevance of the selected 4.420,30 4.733,60 4.854,40 4.720,10 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 2010 2011 2012 2013 2014 2015 2016 2017 2018 2019 2020 BILLION DOLLARS.…”
Section: Literature Reviewmentioning
confidence: 99%